Proceedings of the 2016 International Conference on Civil, Transportation and Environment 2016
DOI: 10.2991/iccte-16.2016.106
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent monitoring method and its experiment for bridge bearing

Abstract: The bridge bearing stress and deformation can eflect the safety of the bridge structure significantly. For bridge bearing status monitoring, identification and early warning technology, in recent years, is an important research direction for structural health monitoring. This paper is based on a model pot rubber bearing , combines with the practical application of bridge bearing condition, chooses specific sensors as data acquisition nodes, designs and develops the signal adjusting module, and uses the data ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Agrawal et al [ 7 ] proposed schemes that use combinations of linear variable differential transformers, pressure sensors, accelerometers, thermocouples, and fibre optic sensors. Other schemes include fibre Bragg grating displacement sensors for bearing condition monitoring [ 12 ], piezoresistive sensors for bearing stress distribution measurement [ 13 ], and polyvinylidene fluoride polymer film−based sensors for vertical reaction measurement [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Agrawal et al [ 7 ] proposed schemes that use combinations of linear variable differential transformers, pressure sensors, accelerometers, thermocouples, and fibre optic sensors. Other schemes include fibre Bragg grating displacement sensors for bearing condition monitoring [ 12 ], piezoresistive sensors for bearing stress distribution measurement [ 13 ], and polyvinylidene fluoride polymer film−based sensors for vertical reaction measurement [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, once the hydraulic pressure entered the steel, the data drifted. Liu et al [17] and Hang et al [18] showed that based on the original structure and mechanical properties of a pot bearing, the internal stress distribution of the bearing was measured by built-in flexible thin-film pressure sensors. The pressure resistance varied with pressure, but the film material was very sensitive to changes in temperature and was prone to signal drift and hysteresis.…”
Section: Introductionmentioning
confidence: 99%